2018
DOI: 10.17341/gazimmfd.416527
|View full text |Cite
|
Sign up to set email alerts
|

EKG verilerinin destek vektör regresyon yöntemiyle sıkıştırılması

Abstract: Highlights:Graphical/Tabular Abstract Purpose: Electrocardiogram (ECG) signals must be continuously recorded and monitored to effectively detect diseases caused by fast or slow heartbeat, that is, rhythm disorders. However, long monitoring periods generates large amount of data that are difficult to store and transmit. Moreover, these records may be subject to noise due to the environment. For this reason, an effective and reliable data compression technique is needed for ECG data compression without losing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Within the ambit of our study, we further augmented the SVR model's capabilities by blending it with the formidable radial basis function (RBF) kernel. This blending process is instrumental in calculating the proximity and similarity between two data points, a critical aspect that underpins SVR's predictive capabilities in our research endeavors [58][59][60]. The judicious combination of SVR and the RBF kernel fortifies the model's capacity to capture intricate patterns and relationships within the data, culminating in a potent tool for accurate prediction and forecasting in our study.…”
Section: Support Vector Regressionmentioning
confidence: 98%
“…Within the ambit of our study, we further augmented the SVR model's capabilities by blending it with the formidable radial basis function (RBF) kernel. This blending process is instrumental in calculating the proximity and similarity between two data points, a critical aspect that underpins SVR's predictive capabilities in our research endeavors [58][59][60]. The judicious combination of SVR and the RBF kernel fortifies the model's capacity to capture intricate patterns and relationships within the data, culminating in a potent tool for accurate prediction and forecasting in our study.…”
Section: Support Vector Regressionmentioning
confidence: 98%
“…Recently, unlike current transform based compression techniques, Karal [10] has proposed a new method based on standard support vector regression (SVR) to compress ECG data according to the given error tolerance in an optimal and rapid manner. It has also been shown that the performance of the proposed standard SVR-based compression technique is higher than that of transform-based compression techniques such as FT, DCT, and DWT commonly used in the literature.…”
Section: Introductionmentioning
confidence: 99%